AUTEKOLOGI AKASIA (Acacia nilotica) (L.) Willd. ex. Del DI TAMAN NASIONAL BALURAN JAWA TIMUR - Djufri Djufri (Universitas Syiah Kuala, 2012)
This research aim to to know : ( 1). Live cycle of A. nilotica, ( 2). Sspreading and Seed production in BNP, ( 3). Potency of A. nilotica as species bioprosfektif, and ( 4) Stand structure of A. nilotica in BNP.Research method used to know cycle live, spreading and seed production in BNP and the done conducted stand structure with direct perception in field. Produce seed used a square method having a nest counted 10 fruit by using plastic. obtained stand structure data with madely is permanent square for the width of 20 m x 20 m of counted 15 fruit, and at each square measured by a diameter and high counted 10 tree. While data to know potency A. nilotica as species biprospektif obtained from data relevant secunder with problems checked.Conclusion from this research is : (1). There are six cycle step live A. nilotica that is seed corps, seedling, juvinile, adult, flower, and seed in pod, ( 2). Production of seed/tree at age 3 year gyrate 506seed/tree. : (3). Seed spreading A. nilotica in BNP through animal like bull, wild buffalo, deer and others, and also water at the rains season, ( 4). Potency of A. nilotica as species bioprospektif can be developed forestry, health, and also industrial, and ( 5). Stand structure A. nilotica in BNP pertained as strightened age.